A Review on Prediction of User Action Interpretation for Online Content Optimization (International Journal of Engineering and Computer Science, 2018)
: Now a day, the use of internet increases tremendously and it has become an important medium to deliver digital content to web users. Most of the vendors may take a help of e-commerce sites to sell their items, but the problem is that how to improve the business, how to attract more web users attention and retain them to their portal sites on an ongoing basis.  To attract more users it is necessary to build recommender system that can help to improve the business by understanding users’ interest. Recommender system provides best items to the consumers by keeping track of their search patterns and online merchants can get a better understanding of their behaviors and intentions. For that purpose, we propose deeper user action interpretation. We take the use of business intelligence, which is the technology for gathering, storing, analyzing, and providing access to data to help enterprise users make better business decisions. We are using Data mining to understand user interest and according to that items will deliver to them. We approach decision support system to generate mining reports and that will help merchant to improve the performance of the system.